Regenerated polyarylene sulfide resin composition, and method for manufacturing the same
The recycled fibrous filler reinforced polyarylene sulfide resin composition effectively addresses the challenges of maintaining mechanical properties and flowability by blending recycled unreinforced PAS resin with optimized amounts of fibrous fillers, resulting in a composition suitable for various industrial applications.
Patent Information
- Application Number
- JP2023164110
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-08
AI Technical Summary
Existing resin compositions using recycled polyarylene sulfide (PAS) resins face challenges in maintaining excellent mechanical properties and flowability, particularly when incorporating recycled fibrous fillers, which can lead to degradation of mechanical properties and reduced efficiency in recycling processes.
A recycled fibrous filler reinforced polyarylene sulfide resin composition is developed, incorporating a specific blend of recycled unreinforced PAS resin and fibrous fillers, optimized to maintain excellent mechanical properties and flowability. The composition includes 100 parts by weight of PAS resin (A) with a melt viscosity of 100 to 3000 poise, combined with 10 to 250 parts by weight of recycled unreinforced PAS resin (B), and 10 to 70 parts by weight of fibrous filler (C).
The resulting recycled fibrous filler reinforced PAS resin composition exhibits excellent impact resistance, mechanical strength, and flowability, making it suitable for applications in electrical and electronic components, automobile parts, and water-related applications without compromising the inherent properties of the PAS resin.
Smart Images

Figure 2025054896000001 
Figure 2025054896000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a recycled fibrous filler-reinforced polyarylene sulfide resin composition containing a recycled unreinforced polyarylene sulfide resin, and relates to a recycled fibrous filler-reinforced polyarylene sulfide resin composition which maintains the excellent properties inherent to polyarylene sulfide resin, such as mechanical properties and fluidity, despite containing unreinforced polyarylene sulfide resin recovered from used products, etc. that are disposed of by incineration, landfill, etc. after market distribution, and unreinforced polyarylene sulfide resin obtained by collecting and regenerating polyarylene sulfide resin, such as unwanted polyarylene sulfide resin generated during the production of polyarylene sulfide resin products, and a method for producing the same. [Background technology]
[0002] Polyarylene sulfide (hereinafter sometimes abbreviated as PAS), represented by poly(p-phenylene sulfide) (hereinafter sometimes abbreviated as PPS), is a resin that exhibits excellent properties such as heat resistance, chemical resistance, and fluidity, and taking advantage of these excellent properties, it is widely used in electrical and electronic equipment components, automotive components, and office equipment components, etc.
[0003] Meanwhile, in recent years, there has been an increasing demand, mainly in Europe and the United States, for the use of recycled resins in electrical and electronic equipment components, with the aim of reducing plastic emissions, and this trend is now spreading to automotive components as well.
[0004] In general, recycled materials are broadly divided into post-consumer recycled materials (hereinafter sometimes abbreviated as PCR) and post-industrial recycled materials (hereinafter sometimes abbreviated as PIR), where PCR refers to materials collected or recycled after a product has been used and discarded by a consumer, and PIR refers to materials collected or recycled from waste generated in the manufacturing process before the product reaches the consumer. Recycled polyarylene sulfide resin obtained by recycling molded bodies discarded after market distribution falls under PCR, while recycled polyarylene sulfide resin obtained by recycling industrial waste such as sprues, runners, or unwanted parts of said molded bodies falls under PIR.
[0005] Examples of resin compositions containing recycled materials include recycled resin compositions used for filament materials for 3D printers using the thermal fusion lamination technique, which are recycled from plastic packaging materials and contain a recycled resin (A) containing a polyolefin resin as the main component and unmelted matter in which the ratio of particles having a maximum diameter of 200 μm or more is 15% or less, and a resin (B) having a melt flow rate of 5 g / 10 minutes or more measured at a temperature of 230° C. and a load of 2.16 kg (see, for example, Patent Document 1). (A) Recycled aromatic polycarbonate resin 40 (E) 0.01 to 1 part by mass of a fluorine compound, and (F) 0.5 to 10 parts by mass of a polyorganosiloxane-containing graft copolymer, per 100 parts by mass in total of (A) 20 to 60% by mass of an aromatic polycarbonate resin and (B) 20 to 60% by mass of an aromatic polycarbonate resin, the polycarbonate resin composition containing no nickel-coated carbon fiber and (C) 10 to 60 parts by mass of a carbon fiber coated with a resin selected from polyamide, polyurethane and epoxy resin, (D) 10 to 20 parts by mass of a phosphate ester compound, (E) 0.01 to 1 part by mass of a fluorine compound, and (F) 0.5 to 10 parts by mass of a polyorganosiloxane-containing graft copolymer, and the like has been proposed (for example, see Patent Document 2).
[0006] Furthermore, as a method for producing a molded article containing recycled materials, there have been proposed, for example, a method for producing a molded article in which 20 to 80% by weight of recycled pellets of a fibrous filler reinforced crosslinked polyphenylene sulfide composition and 80 to 20% by weight of non-recycled pellets of a fibrous filler reinforced crosslinked polyphenylene sulfide composition are fed to an injection molding machine and injection molded (see, for example, Patent Document 3), and a method for producing a glass fiber reinforced recycled PPS resin composition in which crushed molded article containing PPS resin and glass fiber is blended with 40 to 90% by weight of PPS resin having a weight average molecular weight of 20,000 to 60,000 and 10 to 60% by weight of glass fiber (see, for example, Patent Document 4). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent Publication No. 2021-115795 [Patent Document 2] Patent No. 6825890 [Patent Document 3] Patent No. 5386853 [Patent Document 4] Patent No. 7235177 Summary of the Invention [Problem to be solved by the invention]
[0008] However, in the resin compositions proposed in Patent Documents 1 and 2, no consideration or proposal has been made on polyarylene sulfide resins, which are difficult to handle and use, nor on those belonging to the category of super engineering plastics. In addition, in the manufacturing method of molded products proposed in Patent Document 3, only a manufacturing method of molded products is proposed in which recycled pellets of fibrous filler reinforced crosslinked polyphenylene sulfide recycled from unnecessary products and non-regenerated pellets of fibrous filler reinforced crosslinked polyphenylene sulfide composition are fed to an injection molding machine, and the method of utilizing recycled resin is limited. Furthermore, the glass fiber reinforced recycled PPS resin composition proposed in Patent Document 4 has problems such as damage to glass fibers and the like when crushing molded products and when reusing, and deterioration of mechanical properties due to deterioration of resin.
[0009] Therefore, an object of the present invention is to provide a recycled fibrous filler reinforced PAS resin composition containing recycled PAS resin without impairing the mechanical properties, fluidity, etc. that are inherent to PAS resin, and a method for producing the same.
[0010] Furthermore, reusing recycled polyarylene sulfide resin and increasing its efficiency will contribute to the promotion of inclusive and sustainable industrialization, and is one of the technologies that will contribute to a sustainable society, such as the SDGs that have been called for in recent years. [Means for solving the problem]
[0011] As a result of intensive research aimed at solving the above-mentioned problems, the inventors have discovered that when recycled unreinforced PAS resin is used as the recycled PAS resin, a specific recycled fibrous filler reinforced PAS resin composition containing recycled unreinforced PAS resin can have excellent mechanical properties and fluidity, thereby completing the present invention.
[0012] That is, the present invention relates to a recycled fibrous filler-reinforced polyarylene sulfide resin composition, characterized in that it contains 100 parts by weight of a polyarylene sulfide resin (A) having a melt viscosity of 100 to 3,000 poise measured under conditions of a measuring temperature of 315°C and a load of 10 kg using a high-temperature flow tester equipped with a die having a diameter of 1 mm and a length of 2 mm, and contains 10 to 70 parts by weight of a fibrous filler (C) for a total amount of 100 parts by weight consisting of 10 to 250 parts by weight of a recycled unreinforced polyarylene sulfide resin (B).
[0013] The present invention will be described in detail below.
[0014] The PAS resin (A) constituting the recycled fibrous filler reinforced PAS resin composition of the present invention may be any resin that falls within the category generally referred to as a PAS resin. Examples of such PAS resins include homopolymers or copolymers consisting of p-phenylene sulfide units, m-phenylene sulfide units, o-phenylene sulfide units, phenylene sulfide sulfone units, phenylene sulfide ketone units, phenylene sulfide ether units, and biphenylene sulfide units. Specific examples of such PAS resins include PPS, polyphenylene sulfide sulfone, polyphenylene sulfide ketone, and polyphenylene sulfide ether. Of these, PPS is preferred because it results in a recycled fibrous filler reinforced PAS resin composition that has excellent heat resistance and strength properties.
[0015] The PAS resin (A) has a melt viscosity of 100 to 3000 poise, measured at a temperature of 315°C and a load of 10 kg using a high-speed flow tester equipped with a die having a diameter of 1 mm and a length of 2 mm. If the melt viscosity is less than 100 poise, the resulting composition will have poor impact resistance. On the other hand, if the melt viscosity is more than 3000 poise, the resulting composition will have poor flowability.
[0016] The PAS resin (A) can be produced by a method known as a method for producing a PAS resin, for example, by polymerizing an alkali metal sulfide salt and a polyhalogenated aromatic compound in a polar solvent. Examples of the polar organic solvent include N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, cyclohexylpyrrolidone, dimethylformamide, and dimethylacetamide, and examples of the alkali metal sulfide salt include anhydrides or hydrates of sodium sulfide, rubidium sulfide, and lithium sulfide. In addition, the alkali metal sulfide salt may be a product obtained by reacting an alkali metal hydrosulfide salt with an alkali metal hydroxide. Examples of the polyhalogenated aromatic compound include p-dichlorobenzene, p-dibromobenzene, p-diiodobenzene, m-dichlorobenzene, m-dibromobenzene, m-diiodobenzene, 4,4'-dichlorodiphenyl sulfone, 4,4'-dichlorobenzophenone, 4,4'-dichlorodiphenyl ether, and 4,4'-dichlorodibiphenyl.
[0017] The PAS resin (A) may be linear, may be a PAS resin having a small amount of trihalogen or higher polyhalogen compound added during polymerization to introduce a crosslinked or branched structure, may be a PAS resin having a part and / or end modified with a functional group such as a carboxyl group, a carboxy metal salt, an amino group, an alkyl group, an alkoxy group, or a nitro group, may be a PAS resin having a heat treatment in a non-oxidizing inert gas such as nitrogen, or may be a mixture of these structures. The PAS resin (A) may be a PAS resin having a reduced amount of impurities such as sodium atoms, oligomers of PAS resin, table salt, and sodium salt of 4-(N-methyl-chlorophenylamino)butanoate by deionization (acid washing or hot water washing, etc.) before or after heat curing, or by washing with an organic solvent such as acetone or methyl alcohol. The PAS resin (A) may also be a PAS resin having a heat treatment in an inert gas or oxidizing gas after the polymerization reaction is completed to cure the PAS resin.
[0018] The recycled non-reinforced PAS resin (B) constituting the recycled fibrous filler reinforced PAS resin composition of the present invention may be a PAS resin regenerated from industrial waste such as products discarded after market distribution or unnecessary products generated during molding. The recycled non-reinforced PAS resin (B) regenerated from products discarded after market distribution corresponds to PCR, and is excellent in sustainability from the viewpoint of reducing resource consumption, etc., and its use is expected. The recycled non-reinforced PAS resin (B) regenerated from unnecessary products during molding corresponds to PIR, and since PAS resins of the same structure, the same grade, and even the same lot in some cases can be recycled, it becomes a recycled non-reinforced PAS resin with small quality variation, and it is possible to obtain a recycled fibrous filler reinforced PAS resin composition with small quality variation. The recycled PAS resin in this case is a non-reinforced PAS resin. Here, in the case of a reinforced PAS resin composition containing a fibrous filler, not only does the filler, etc., break during recycling, but the mechanical properties are likely to decrease due to resin deterioration caused by heat generated by the blending of the filler, etc. Examples of the recycled non-reinforced PAS resin (B) include commercially available PAS resin fibers, PAS resin sheets, PAS resin films, and further products using these that have been subjected to recycling.
[0019] The amount of the recycled non-reinforced PAS resin (B) is 10 to 250 parts by weight per 100 parts by weight of PAS resin (A), because the mechanical properties such as impact resistance are not significantly deteriorated even if the proportion of recycled material is increased. Here, if the amount of the recycled non-reinforced PAS resin (B) is less than 10 parts by weight, the proportion of recycled material is low, and the significance of reuse is reduced. On the other hand, if it exceeds 250 parts by weight, the resulting composition will be inferior in impact resistance and fluidity.
[0020] The fibrous filler (C) constituting the recycled fibrous filler reinforced PAS resin composition of the present invention may be any that belongs to the category of fibrous fillers, such as glass fiber; carbon fiber such as PAN-based carbon fiber and pitch-based carbon fiber; graphitized fiber; whiskers such as silicon nitride whiskers, basic magnesium sulfate whiskers, barium titanate whiskers, potassium titanate whiskers, silicon carbide whiskers, boron whiskers, zinc oxide whiskers; metal fibers such as stainless steel fibers; inorganic fibers such as rock wool, zirconia, alumina silica, barium titanate, silicon carbide, alumina, silica, blast furnace slag; organic fibers such as fully aromatic polyamide fibers, phenolic resin fibers, fully aromatic polyester fibers; mineral fibers such as wollastonite and magnesium oxysulfate, etc., and glass fiber is preferable because it is a recycled fibrous filler reinforced PAS resin composition with excellent mechanical strength and impact resistance. As the glass fiber, any fiber generally called glass fiber may be used. Specific examples of the glass fiber include chopped strands having an average fiber diameter of 6 to 14 μm, chopped strands made of flat glass fibers having an aspect ratio of the fiber cross section of 2 to 4, milled fibers, glass fibers such as rovings, silane fibers, aluminosilicate glass fibers, hollow glass fibers, non-enamel glass fibers, etc., and among these, chopped strands having an average fiber diameter of 6 to 14 μm or chopped strands made of flat glass fibers having an aspect ratio of the fiber cross section of 2 to 4 are preferable because they provide a recycled fibrous filler reinforced PAS resin composition having excellent mechanical strength, impact resistance, and flowability. Two or more of these fibrous fillers can be used in combination, and if necessary, they may be surface-treated in advance with a functional compound or polymer such as an epoxy compound, an isocyanate compound, a silane compound, or a titanate compound. The amount of the fibrous filler (C) to be blended is 10 to 70 parts by weight per 100 parts by weight of the combined amount of PAS resin (A) and recycled unreinforced PAS resin (B), in order to obtain a recycled fibrous filler-reinforced PAS resin composition having an excellent balance of toughness, mechanical strength, and fluidity.If the amount of the fibrous filler is less than 10 parts by weight, the resulting composition will have poor impact resistance, whereas if it exceeds 70 parts by weight, the resulting composition will have poor fluidity.
[0021] The recycled fibrous filler-reinforced PAS resin composition of the present invention is preferably made to have excellent toughness by containing a thermoplastic elastomer (D). As the thermoplastic elastomer (D), any material generally called a thermoplastic elastomer may be used, and it may be a thermoplastic elastomer having a reactive functional group, a thermoplastic elastomer not having a reactive functional group, or a mixture of a thermoplastic elastomer having the reactive functional group and a thermoplastic elastomer not having the reactive functional group. Examples of the reactive functional group include an epoxy group, a maleic anhydride group, a carboxylic acid group, an amino group, an isocyanate group, and the like. Examples of the thermoplastic elastomer having the reactive group include modified ethylene copolymers such as ethylene-α,β-unsaturated carboxylic acid alkyl ester-maleic anhydride copolymer, ethylene-α,β-unsaturated carboxylic acid glycidyl ester copolymer, ethylene-α,β-unsaturated carboxylic acid glycidyl ester-vinyl acetate copolymer, ethylene-α,β-unsaturated carboxylic acid glycidyl ester-α,β-unsaturated carboxylic acid alkyl ester copolymer, maleic anhydride graft-modified ethylene-α-olefin copolymer, hydrogenated styrene-butadiene-styrene block copolymer modified with maleic anhydride or its derivative, styrene-butadiene-styrene block copolymer modified with maleic anhydride or its derivative, and the like. Examples of the hydrogenated vinyl aromatic compound block copolymer include hydrogenated ethylene-butadiene block copolymer modified with maleic anhydride or its derivative, hydrogenated styrene-isoprene block copolymer modified with maleic anhydride or its derivative, and hydrogenated styrene-isoprene-styrene block copolymer modified with maleic anhydride or its derivative. In addition, as long as it has a functional group reactive with the PAS resin, polyurethane thermoplastic elastomer, polyester thermoplastic elastomer, polyamide thermoplastic elastomer, acrylonitrile-butadiene rubber thermoplastic elastomer, ethylene-propylene copolymer, ethylene-propylene-diene copolymer, etc. can also be used. Among these, modified ethylene copolymers are preferred because they provide a recycled fibrous filler reinforced PAS resin composition with excellent toughness.
[0022] On the other hand, examples of thermoplastic elastomers that do not have reactive functional groups include the above-mentioned thermoplastic elastomers that do not have functional groups, and among them, olefin-acrylate binary copolymers are preferred because they provide a recycled fibrous filler-reinforced PAS resin composition that is particularly well-balanced between fluidity and toughness. In this case, the olefin may be ethylene or an α-olefin having 3 or more carbon atoms, and the acrylate may be methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, t-butyl acrylate, isobutyl acrylate, etc.
[0023] The amount of the thermoplastic elastomer (D) to be blended is preferably 1 to 20 parts by weight per 100 parts by weight of the total amount of the PAS resin (A) and the recycled unreinforced PAS resin (B), since this results in a recycled fibrous filler reinforced PAS resin composition with an excellent balance of toughness and fluidity.
[0024] The recycled fibrous filler-reinforced PAS resin composition of the present invention is particularly excellent in mechanical strength and impact resistance, so it is preferable that it further contains a compatibilizer (E). Examples of the compatibilizer include isocyanurates, epoxy resins, silane coupling agents, and mixtures thereof.
[0025] The isocyanurate may be any that is called an isocyanurate, and among these, aliphatic isocyanurates are preferable because they result in a recycled fibrous filler reinforced PAS resin composition that is less likely to contaminate the mold. Specific examples of the aliphatic isocyanurate include 1,3,5-tris(6-isocyanatohex-1-yl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,3,5-tris(6-isocyanatotetra-1-yl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and 1,3,5-tris(6-isocyanatododec-1-yl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione. Aliphatic isocyanurates with a molecular weight of 500 or more are preferred because they result in a recycled fibrous filler reinforced PAS resin composition that is particularly prone to mold contamination. The aliphatic isocyanurate may be a multimer such as a dimer or trimer, or an isocyanurate containing a multimer such as a dimer or trimer in an aliphatic isocyanurate monomer, and is preferably an aliphatic isocyanurate containing 20% or more isocyanate groups, since this gives a recycled fibrous filler-reinforced PAS resin composition that has excellent reactivity with the PAS resin (A), the recycled non-reinforced PAS resin (B), and in some cases the thermoplastic elastomer (D) and has excellent impact resistance.
[0026] The aliphatic isocyanurate may be a modified aliphatic isocyanate partially modified with alcohol such as 1,3-butanediol or 2,2,4-trimethyl-1,3-pentanediol. Among the aliphatic isocyanurates, 1,3,5-tris(6-isocyanatohex-1-yl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione is particularly preferred because of its excellent cold and heat resistance and easy availability. Specific examples of 1,3,5-tris(6-isocyanatohex-1-yl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione include (trade name) Coronate HXR (manufactured by Tosoh Corporation) and (trade name) Duranate TPA-100 (manufactured by Asahi Kasei Corporation).
[0027] As the epoxy resin, any epoxy resin may be used as long as it belongs to the category called epoxy resin. Specific examples include 2,2-bis(4'-hydroxyphenyl)propane (bisphenol A), bis(2-hydroxyphenyl)methane (bisphenol F), 4,4'-dihydroxydiphenylsulfone (bisphenol S), 4,4'-dihydroxybiphenyl, resorcin, saligenin, trihydroxydiphenyldimethylmethane, tetraphenylolethane, halogen-substituted and alkyl-substituted versions of these, butanediol, ethylene glycol, erythritol, novolac, glycerin, polyoxyalkylene, and other compounds having two or more hydroxyl groups in the molecule, and compounds synthesized from epichlorohydrin, etc. glycidyl ether-based epoxy resins synthesized from a compound containing two or more hydroxyl groups in the molecule and glycidyl phthalate, etc.; glycidyl amine-based epoxy resins synthesized from a primary or secondary amine such as aniline, diaminodiphenylmethane, metaxylenediamine, 1,3-bisaminomethylcyclohexane, etc. and epichlorohydrin, etc., containing glycidyl groups; and epoxy resins not containing glycidyl groups such as epoxidized soybean oil, epoxidized polyolefin, vinylcyclohexene dioxide, dicyclopentadiene dioxide, etc. Among them, bisphenol-type epoxy resins such as glycidyl ether-based epoxy resins and glycidyl ester-based epoxy resins of bisphenols such as bisphenol A, bisphenol F, bisphenol S, etc. are preferred because the impact resistance of the resulting recycled fibrous filler-reinforced PAS resin composition is particularly excellent. Bisphenol A-type epoxy resins are even more preferred.
[0028] Furthermore, the silane coupling agent may be any agent that falls within the category known as a silane coupling agent. Among these, it is preferable to use a silane coupling agent consisting of a trialkoxysilane coupling agent having a glycidyl group and / or a trialkoxysilane coupling agent having an amino group, since this results in a recycled fibrous filler reinforced PAS resin composition that has excellent impact resistance and mechanical strength. The silane capping agent used in this case is not particularly limited as long as it is a trialkoxysilane coupling agent having a glycidyl group or an amino group, and specific examples belonging to this category include 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, and the like.
[0029] The amount of the compatibilizer (E) to be blended is preferably 0.1 to 15 parts by weight per 100 parts by weight of the combined amount of the PAS resin (A) and the recycled unreinforced PAS resin (B), since this results in a recycled fibrous filler-reinforced PAS resin composition that has excellent impact resistance and mechanical strength and is less likely to contaminate the mold.
[0030] Furthermore, the recycled fibrous filler reinforced PAS resin composition of the present invention may contain a mold release agent (F) to improve mold releasability and appearance when molded into a molded product. As the mold release agent (F), for example, polyethylene wax, polypropylene wax, and fatty acid amide wax are preferably used. As the polyethylene wax and polypropylene wax, general commercial products can be used. In addition, the fatty acid amide wax is a polycondensation product of higher aliphatic monocarboxylic acid, polybasic acid, and diamine, and any wax that falls within this category can be used, such as (trade name) Light Amide WH-255 (manufactured by Kyoeisha Chemical Co., Ltd.), which is a polycondensation product of stearic acid, sebacic acid, and ethylenediamine.
[0031] The recycled fibrous filler reinforced PAS resin composition of the present invention may be used by mixing various additives within the scope of the present invention, for example, one or more of conventional additives such as plasticizers such as polyalkylene oxide oligomer compounds, thioether compounds, ester compounds, and organic phosphorus compounds, antioxidants, heat stabilizers, ultraviolet inhibitors, foaming agents, and pigments such as carbon black may be added. Furthermore, it may be used by mixing one or more of thermoplastic resins such as various thermosetting resins, cyanate ester resins, phenolic resins, polyimides, silicone resins, polyesters, polyphenylene oxides, polycarbonates, polysulfones, polyetherimides, polyethersulfones, polyetherketones, polyetheretherketones, polyamideimides, and polyalkylene oxides.
[0032] The method for producing the PAS resin composition reinforced with recycled fibrous fillers of the present invention can be a conventionally used heating melt kneading method. For example, a heating melt kneading method using a single-screw or twin-screw extruder, kneader, mill, Brabender, etc. can be used. In particular, a melt kneading method using a twin-screw extruder with excellent kneading ability is preferred. In this case, the screw used in the twin-screw extruder preferably has two or more kneading zones. Furthermore, in order to sufficiently knead the PAS resin (A) and the recycled non-reinforced PAS resin (B) and, as a result, to obtain a PAS resin composition reinforced with recycled fibrous fillers with excellent toughness such as impact resistance, it is preferable that the ratio (L1 / D1) of the screw length (L1) to the screw diameter (D1) is 30 or more, particularly 40 or more.
[0033] The cylinder temperature of the kneading zone of the extruder is preferably set to 280 to 330°C, particularly preferably 290 to 320°C, in order to ensure sufficient kneading of the PAS resin (A) and the recycled non-reinforced PAS resin (B) and to easily suppress thermal decomposition of the recycled non-reinforced PAS resin (B). The peripheral speed of the screw is preferably 50 to 400 mm / sec, particularly preferably 150 to 300 mm / sec, in order to ensure good kneading and uniformity of the PAS resin phase and the recycled non-reinforced PAS resin phase of the recycled fibrous filler reinforced PAS resin composition, resulting in a recycled fibrous filler reinforced PAS resin composition with excellent toughness such as impact resistance. The residence time of the molten resin in the extruder is preferably 30 to 100 seconds, particularly preferably 30 to 80 seconds, in order to ensure sufficient melt kneading time of the PAS resin (A) and the recycled non-reinforced PAS resin (B) and to easily suppress thermal decomposition of the recycled non-reinforced PAS resin (B).
[0034] The melt-kneaded recycled fibrous filler reinforced PAS resin composition can be pelletized by hot cutting, mist cutting, or the like of the extruded melt-kneaded product, or cold cutting of the strands, etc., and it is preferable to use cold cutting or hot cutting, in which the melt-kneaded product is cooled by water cooling, air cooling, or the like to form strands, and the strands are cut to form pellets, since this allows stable and efficient production of pellets with excellent quality and color tone. In this case, the pellets are preferably cylindrical pellets with a diameter of 0.5 to 2.5 mm and a length of 1.5 to 4 mm, or spherical pellets with a diameter of 1 to 3 mm, since they provide excellent processability when injection molding various molded products, and it is preferable to use pellets with a light brown or brown color tone, since this allows production of molded products with excellent product appearance.
[0035] Furthermore, the recycled fibrous filler reinforced PAS resin composition of the present invention can be molded into any shape using an injection molding machine, extrusion molding machine, transfer molding machine, compression molding machine, blow molding machine, etc.
[0036] The recycled fibrous filler reinforced PAS resin composition of the present invention contains recycled unreinforced PAS resin without impairing the heat resistance, chemical resistance, fluidity, etc. that are inherent to PAS resin, and is suitable for use in electrical and electronic parts, automotive parts, and water-related applications such as piping and fittings. Effect of the Invention
[0037] According to the present invention, it is possible to provide a recycled fibrous filler reinforced PAS resin composition containing recycled unreinforced PAS resin. The recycled fibrous filler reinforced PAS resin composition has excellent impact resistance and fluidity and is particularly useful for applications such as electric and electronic parts, automobile parts and water-related applications, and therefore has extremely high industrial value. EXAMPLES
[0038] The present invention will be specifically described below with reference to examples, but the present invention is not limited thereto.
[0039] The polyarylene sulfide resin (A), recycled non-reinforced polyarylene sulfide resin (B), fibrous filler (C), thermoplastic elastomer (D), compatibilizer (E), and mold release agent (F) used in the examples and comparative examples are shown below.
[0040] <Polyarylene sulfide resin (A)> Poly(p-phenylene sulfide) (hereinafter referred to as PPS (A-1)); melt viscosity 2500 poise. Amino group-substituted poly(p-phenylene sulfide) (hereinafter referred to as PPS (A-2)); amino group content 0.1 mol%, melt viscosity 1200 poise. Poly(p-phenylene sulfide) (hereinafter referred to as PPS (A-3)); melt viscosity 3220 poise. Poly(p-phenylene sulfide) (hereinafter referred to as PPS (A-4)); melt viscosity 80 poise.
[0041] <Recycled non-reinforced polyarylene sulfide resin (B)> Post-consumer recycled non-reinforced PPS resin (hereinafter referred to as PCRPPS resin (B-1)); manufactured by Ningbo Topcentral New Material CO., Ltd., (trade name) rPPS-B103. Post-industrial recycled non-reinforced PPS resin (hereinafter referred to as PIRPPS resin (B-2)); (trade name) Susteil B-060P (manufactured by Tosoh Corporation; non-reinforced PPS resin) ground product of sprue and runner when injection molded.
[0042] <Fibrous filler (C)> Glass fiber (C-1); manufactured by Central Glass Fiber Co., Ltd., (trade name) ECS03-630; average fiber diameter 9 μm, average fiber length 3 mm. Glass fiber (C-2); manufactured by Nippon Electric Glass Co., Ltd., (trade name) T-760H; fiber diameter 10 μm, fiber length 3 mm. Glass fiber (C-3); manufactured by Nitto Boseki Co., Ltd., (product name) CSG 3PL-830S; aspect ratio 2. Glass fiber (C-4); manufactured by Nippon Electric Glass Co., Ltd., (product name) ECS03T-747-FGF; aspect ratio 4.
[0043] <Thermoplastic elastomer (D)> Ethylene-α,β-unsaturated carboxylic acid glycidyl ester-α,β-unsaturated carboxylic acid alkyl ester copolymer (D-1) (hereinafter simply referred to as thermoplastic elastomer (D-1)); SK Global Chemical Co., Ltd., (product name) LOTADER AX8700, ethylene residue unit: α,β-unsaturated carboxylic acid glycidyl ester residue unit: α,β-unsaturated carboxylic acid alkyl ester residue unit (weight ratio) = 67:8:25.
[0044] <Compatibilizer (E)> Trialkoxysilane coupling agent (E-1) having a glycidyl group (hereinafter referred to as compatibilizer (E-1)); (product name) KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.; 3-glycidoxypropyltrimethoxysilane.
[0045] <Release agent (F)> Release agent (F-1): Nikko Rica Corporation, (product name) Refined Carnauba Powder No. 1. Release agent (F-2): Kyoeisha Chemical Co., Ltd. (product name) Light Amide WH-255.
[0046] Synthesis Example 1 Add flake sodium sulfide (Na 2 SO 4 ) to a 15-liter autoclave equipped with a stirrer. 2 S 2.9H 21814g of O), 8.7g of granular caustic soda (100% NaOH; Wako Pure Chemical special grade) and 3232g of N-methyl-2-pyrrolidone were charged, and the temperature was gradually raised to 200°C while stirring under a nitrogen stream, and 339g of water was distilled off. After cooling to 190°C, 2129g of p-dichlorobenzene and 1783g of N-methyl-2-pyrrolidone were added, and the system was sealed under a nitrogen stream. The system was heated to 225°C over 2 hours, polymerized at 225°C for 1 hour, then heated to 250°C over 25 minutes, and polymerized at 250°C for 2 hours. Next, 509g of distilled water was injected into the system at 250°C, and the temperature was raised to 255°C, and the polymerization reaction was carried out for another 2 hours. After the polymerization was completed, the system was cooled to room temperature, and the polymerized slurry was separated into solid and liquid using a centrifugal filter. The cake was washed three times with N-methyl-2-pyrrolidone and acetone under a nitrogen stream, and then washed with 0.2% hydrochloric acid and warm water under a nitrogen stream. The resulting poly(p-phenylene sulfide) was dried overnight at 105°C to obtain PPS (A-1) with a melt viscosity of 350 poise.
[0047] Synthesis Example 2 Add flake sodium sulfide (Na 2 SO 4 ) to a 50-liter autoclave equipped with a stirrer. 2 S 2.9H 26214g of O) and 17000g of N-methyl-2-pyrrolidone were charged, and the temperature was gradually raised to 205°C while stirring under a nitrogen stream, and 1355g of water was distilled off. After cooling this system to 140°C, 7278g of p-dichlorobenzene, 11.7g of 3,5-dichloroaniline, and 5000g of N-methyl-2-pyrrolidone were added, and the system was sealed under a nitrogen stream. The system was heated to 225°C over 2 hours, polymerized at 225°C for 2 hours, then heated to 250°C over 30 minutes, and polymerized at 250°C for 3 hours. After the polymerization was completed, the system was cooled to room temperature and the polymer was isolated by a centrifuge. The solid content was repeatedly washed with warm water and dried at 100°C for a day and night to obtain an amino-substituted poly(p-phenylene sulfide) with a melt viscosity of 400 poise. Next, the dried amino group-substituted poly(p-phenylene sulfide) was loaded into a batch-type rotary kiln-type calcination apparatus and cured for 2 hours at 240°C in an air atmosphere to obtain PPS (A-2) with a melt viscosity of 1,200 poise and an amino group content of 0.1 mol% relative to the phenyl groups.
[0048] Synthesis Example 3 In a 50-liter autoclave equipped with a stirrer, add Na 2 S 2.9H 2 6214g of O and 17000g of N-methyl-2-pyrrolidone were charged, and the temperature was gradually raised to 205°C while stirring under a nitrogen stream, and 1355g of water was distilled off. After cooling this system to 140°C, 7180g of p-dichlorobenzene and 5000g of N-methyl-2-pyrrolidone were added, and the system was sealed under a nitrogen stream. The system was heated to 225°C over 2 hours, polymerized at 225°C for 2 hours, then heated to 250°C over 30 minutes, and polymerized at 250°C for 3 hours. After the polymerization was completed, the system was cooled to room temperature, and the solid content was isolated by a centrifuge. The solid content was washed with hot water at 180°C and dried at 100°C for a whole day and night to obtain poly(p-phenylene sulfide).
[0049] The resulting poly(p-phenylene sulfide) was cured in an air atmosphere at 250°C for 6 hours to obtain a branched poly(p-phenylene sulfide) (hereinafter referred to as PPS (A-3)). The melt viscosity of PPS (A-3) was 3220 poise.
[0050] Synthesis Example 4 In a 15-liter autoclave equipped with a stirrer, add Na 2 S 2.9H 2 1814g of O, 8.7g of granular caustic soda (100% NaOH; Wako Pure Chemical special grade) and 3232g of N-methyl-2-pyrrolidone were charged, and the temperature was gradually raised to 200°C while stirring under a nitrogen stream, and 339g of water was distilled off. After cooling this system to 190°C, 2085g of p-dichlorobenzene and 1783g of N-methyl-2-pyrrolidone were added, and the system was sealed under a nitrogen stream. The system was heated to 225°C over 2 hours, polymerized at 225°C for 1 hour, then heated to 250°C over 25 minutes, and polymerized at 250°C for 2 hours. After the polymerization was completed, the system was cooled to room temperature, and the solid content was isolated by a centrifuge. The solid content was washed with hot water at 180°C and dried at 105°C for a whole day and night to obtain poly(p-phenylene sulfide).
[0051] The poly(p-phenylene sulfide) thus obtained was dried at 240°C for 6 hours under reduced pressure using a vacuum dryer to obtain a linear poly(p-phenylene sulfide) (hereinafter referred to as PPS (A-4)). The melt viscosity of PPS (A-4) was 80 poise.
[0052] The evaluation and measurement methods for the obtained PAS resin composition are shown below.
[0053] ~Melt viscosity measurement of PAS resin~ The melt viscosity was measured using a high-temperature flow tester (manufactured by Shimadzu Corporation, product name CFT-500) equipped with a die having a diameter of 1 mm and a length of 2 mm, under conditions of a measurement temperature of 315° C. and a load of 10 kg.
[0054] ~Measurement of Charpy impact strength (notched)~ Test pieces were prepared using an injection molding machine (manufactured by Sumitomo Heavy Industries, Ltd., product name: SE-75S) and measurements were performed in accordance with ISO 179-1. Charpy impact strength: 8 kJ / m 2 The above items were deemed to have excellent impact resistance.
[0055] ~Measurement of liquidity~ A mold with a spiral groove of 1 mm thickness and 10 mm width was attached to an injection molding machine (product name: SE-75S, manufactured by Sumitomo Heavy Industries, Ltd.), and the PAS resin composition was then loaded into the hopper of the injection molding machine with the cylinder temperature set to 310°C, injection pressure set to 190 MPa, injection speed set to maximum, injection time set to 1.5 seconds, and mold temperature set to 135°C, and injected. The length of the molten material that flowed through the spiral groove in the mold was measured as molding fluidity. Molding fluidity of more than 120 mm was judged to be excellent fluidity.
[0056] Example 1 100 parts by weight of the PPS (A-1) obtained in Synthesis Example 1 and 20 parts by weight of PCR PPS resin (B-1) were uniformly mixed in advance and charged into the hopper of a twin-screw extruder (manufactured by The Japan Steel Works, Ltd., (product name) TEX-25αIII, L1 / D1=55) having four kneading zones. On the other hand, 78 parts by weight of glass fiber (C-1) per 100 parts by weight of PPS resin (A-1) (corresponding to 65 parts by weight per 100 parts by weight of PPS resin (A-1) and PCR PPS resin (B-1) in total) and 3 parts by weight of release agent (F-1) were added from the hopper of the side feeder of the twin-screw extruder, and melt-kneaded at a raw material supply rate of 25 kg / hr and a screw rotation speed of 200 rpm (circumferential speed: 258 mm / sec) under conditions where the cylinder temperature of the kneading zone was heated to 300°C, and the molten recycled fibrous filler reinforced PAS resin composition flowed out of the die with a residence time of 50 seconds was water-cooled and made into strands, which were then cut into pellets having a cylindrical shape with a diameter of 0.5 to 2.5 mm and a length of 1.5 to 4 mm, to obtain a recycled fibrous filler reinforced PAS resin composition.
[0057] The resulting recycled fibrous filler-reinforced PAS resin composition was then placed in an injection molding machine (manufactured by Sumitomo Heavy Industries, Ltd., product name: SE75S) heated to a cylinder temperature of 300°C and a mold temperature of 140°C, and the molding flow length of the recycled fibrous filler-reinforced PAS resin composition was measured. Furthermore, the Charpy impact strength was evaluated using the injection-molded test pieces. The results of each measurement and evaluation are shown in Table 1.
[0058] Examples 2 to 9 A pellet-shaped recycled fibrous filler-reinforced PAS resin composition was obtained in the same manner as in Example 1, except that the blending ratios of PAS resin (A-1, -2), PCRPPS resin (B-1), PIRPPS resin (B-2), glass fiber (C-1 to -4), thermoplastic elastomer (D-1), compatibilizer (E-1), and release agent (F-1, -2) were set as shown in Table 1. The pellets were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.
[0059] All the obtained recycled fibrous filler reinforced PAS resin compositions had excellent impact resistance and flowability.
[0060] [Table 1]
[0061] Comparative Examples 1 to 6 A pellet-shaped resin composition was obtained in the same manner as in Example 1, except that the blending ratios of PPS (A-1, -2, -3, -4), PCR PPS resin (B-1), glass fiber (C-1, -2), thermoplastic elastomer (D-1), compatibilizer (E-1), and release agent (F-1, -2) were set as shown in Table 2. The pellet-shaped resin composition was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 2.
[0062] The resin compositions obtained in Comparative Examples 2, 4, and 6 were poor in impact resistance. The resin compositions obtained in Comparative Examples 1, 3, and 5 were poor in fluidity.
[0063] [Table 2] [Industrial Applicability]
[0064] The recycled fibrous filler reinforced PAS resin composition of the present invention contains recycled unreinforced PAS resin without impairing the mechanical properties and fluidity that are inherent to PAS resin, and is particularly useful in applications such as electric and electronic parts, automobile parts, and water-related applications such as piping and fittings.
Claims
1. A recycled fibrous filler-reinforced polyarylene sulfide resin composition comprising 100 parts by weight of a polyarylene sulfide resin (A) having a melt viscosity of 100 to 3,000 poise measured under conditions of a measuring temperature of 315°C and a load of 10 kg using a high-performance flow tester equipped with a die having a diameter of 1 mm and a length of 2 mm, and 10 to 70 parts by weight of a fibrous filler (C) for a total amount of 100 parts by weight consisting of 10 to 250 parts by weight of a recycled non-reinforced polyarylene sulfide resin (B).
2. The recycled fibrous filler reinforced polyarylene sulfide resin composition according to claim 1, characterized in that the recycled non-reinforced polyarylene sulfide resin (B) is a post-consumer recycled polyarylene sulfide resin and / or a post-industrial recycled polyarylene sulfide resin.
3. The recycled fibrous filler-reinforced polyarylene sulfide resin composition according to claim 1, characterized in that the recycled non-reinforced polyarylene sulfide resin (B) is a recycled product of polyarylene sulfide resin fiber, polyarylene sulfide resin sheet, or polyarylene sulfide resin film.
4. The recycled fibrous filler-reinforced polyarylene sulfide resin composition according to claim 1, characterized in that the fibrous filler (C) is a fibrous filler having an average fiber diameter of 6 to 14 μm and / or a fiber cross-sectional aspect ratio of 2 to 4.
5. The recycled fibrous filler reinforced polyarylene sulfide resin composition according to claim 1, further comprising a thermoplastic elastomer (D), a compatibilizer (E) and / or a release agent (F).
6. A pellet made of the recycled fibrous filler reinforced polyarylene sulfide resin composition according to claim 1 or 2, characterized in that it has a cylindrical shape with a diameter of 0.5 to 2.5 mm and a length of 1.5 to 4 mm or a spherical shape with a diameter of 1 to 3 mm.
7. A method for producing a recycled fibrous filler-reinforced polyarylene sulfide resin composition, comprising melt-kneading and extruding at least a polyarylene sulfide resin (A), a recycled non-reinforced polyarylene sulfide resin composition (B) and a fibrous filler (C) in a twin-screw extruder having a screw with a screw length (L1) to screw diameter (D1) ratio (L1 / D1) of 30 or more and two or more kneading zones under kneading conditions of a cylinder temperature in the kneading zone of 280 to 330°C, a peripheral speed of the screw of 50 to 400 mm / sec and a residence time of 30 to 100 seconds.
Citation Information
Patent Citations
Method of monitoring yarn tension
JP1978086853A
Recycled resin composition
JP2021115795A
Polycarbonate resin composition
JP6825890B2
Method for producing glass fiber reinforced recycled polyphenylene sulfide resin composition, and molded article obtained by molding the glass fiber reinforced recycled polyphenylene sulfide resin composition
JP7235177B1